Association Between Subjects with Newly Diagnosed Rheumatoid Arthritis and Dental Caries - Sánchez-Medrano, Ana Gabriela; Martínez-Gutiérrez, Fidel; Martínez-Martínez, Marco Ulises; Salas-Orozco, Marco Felipe; Villa-García, Lorena Dafnee; Patiño-Marín, Nuria (Odovtos - International Journal of Dental Sciences, 2021)
Alterations in saliva, temporomandibular joint disorders, dysphagia, Sjogren's syndrome, dental caries, periodontal disease, and tooth loss have been identified in patients with Rheumatoid Arthritis. The aims of this research were 1) to study the association between newly diagnosed rheumatoid arthritis and dental caries and 2) to identify most frequent teeth with caries in study groups. A descriptive pilot study was performed. A total of 620 participants were evaluated, 29 met the selection criteria. The subjects were divided into 2 groups: 13 subjects with newly diagnosed rheumatoid arthritis and 16 subjects without rheumatoid arthritis. Salivary parameters, DMFT index, care index, FS-T index and Treatment Needs Index were evaluated in all participants. The Fisher’s Exact test and Mann-Whitney U test we used to establish the differences between groups. Low mean in all salivary parameters and a high caries frequency were observed in subjects with newly diagnosed rheumatoid arthritis compared to a control group (p<0.01). The right maxillary second premolar (n=6, 46%, p=0.0100); right mandibular second premolar (n=7,54%, p=0.0462) and left mandibular second molar (n=10,77%, p=0.0001) were the most frequent teeth with caries. Early diagnosis and early treatment of rheumatoid arthritis can improve the prognosis in most of patients. The development of new public health policies and care based on the prevention are necessary to improve the quality of patient's lives.